Вплив гемодинамічних зсувів на розвиток та перебіг регматогенних відшарувань сітківки - Завгородня, Наталія Григорівна; Дєдов, А. В.; Івахненко, Олена Михайлівна; Zavgorodnya, N. H.; Dedov, A.; Ivakhnenko, O. M. (My University, 2016)
Для оцінки ступеня порушень очної гемодинаміки при регматогенних відшаруваннях сітківки та їх впливу на результати лікування екстрасклеральними методами обстежено 92 хворих з відшаруванням сітківки та 24 хворих з міопією (всього 232 ока). Виявлено: значний гемодинамічний дефіцит в очах з відшаруванням сітківки, тісний зворотний зв’язок між передньо-заднім розміром ока та рівнем кровотоку в ньому, що свідчить про доцільність заходів з корекції гемодинамічних порушень під час лікування відшарувань сітківки екстрасклеральними методами. There is an evidence of development of retinal detachment against decrease in regional blood fl ow in literature, so degree of circulatory disorders in the eye with retinal detachment assessment is actual to develop a set of correction methods for these conditions in the future. Aim. Assessment of degree of violation of regional hemodynamics in patients with retinal detachment relatively to patients with myopia and the impact of these disorders on the results of extrascleral surgical treatment methods. Materials and Methods. There were examined 92 patients with retinal detachment and 24 patients with myopia (232 eyes). Main group: 92 patients with rhegmatogenous retinal detachment, 54,3% of women, mean age 55,12±1,34 years, BCVA 0,13±0,02, visual fi elds 274,24±13,44 degrees (summary in 8 meridians). Reoophthalmography and ultrasound dopplerography were performed. Control group included fellow eyes of the same patients, eyes without rhegmatogenous retinal detachment, BCVA 0,92±0,05, visual fi elds 502,46±17,23 degrees (summary in 8 meridians). Group of comparison consisted of patients with myopia from 14,5 D to –0,5 D (–3,37±0,51) D without signs of chorioretinal dystrophy, 58,3% of women, mean age 53,58±1,24 years, BCVA 0,89±0,04, visual fi elds 497,76±14,95 degrees (summary in 8 meridians).
Influence of hemodynamic disorders in development and progress of rhegmatogenous retinal detachment
Keywords: відшарування сітківки; реґіонарний кровоток; екстрасклеральні втручання; rhegmatogenous retinal detachment; regional blood flow; extrascleral methods